Persepsi Siswa Terhadap Penggunaan Media Audio-visual pada Pembelajaran Matematika - Siti Riva; Rhomiy Handican (Griya Journal of Mathematics Education and Application, 2023)
Audiovisual learning media is one of the teaching media used by teachers to make learning easier to understand. This research aims to see students' perceptions of the application of audiovisual learning media in mathematics learning subjects. This research is descriptive qualitative where this research will analyze the opinions of 28 students who were sampled. In this study, questionnaires were used to collect data on students' perceptions. Examining the data descriptive method was used. Based on the results of the study, it is known that students' perceptions of the application of audiovisual learning media make it easier for students to understand mathematics learning concepts are at a good level where 64.3% of students agree that the application of audiovisual learning media makes it easier for students to understand mathematics concepts. In addition, 78.6% of students also stated that the use of audiovisual learning media can make learning more interesting, and also 71.4% of students stated that the use of audiovisual learning media can provide a clearer picture of mathematics learning material. Therefore, the existence of audiovisual learning media is very helpful for a teacher during the teaching and learning process so that learning becomes fun.